Proposed Product Design of Solar Street Lighting System Using Quality FUnction Deployment (QFD) Method in PT Solare Bandung - Prabowo, Wisnu Ajie; Aldianto, Leo (The Indonesian Journal of Business Administration, 2013)
The emergence of competition in business is inevitable. With competition, every company faced with both opportunities and threats coming from outside or from within the country. Companies should seek to minimize their weaknesses and maximize strengths. Thus the company is required to select and define strategies that can be used to deal within the competition. PT SOLARE was established in 2004, as a manufacturer of solar home lighting system and at 2007 manufacture a street lighting system. PT SOLARE has never achieved sales target of street lighting system that defined by the management. That was an impact of the intense competition in the industry. It also because PT SOLARE was unable to achieved customer needs and wants from the street lighting system. Root cause need to be determined to know why PT SOLARE unable to achieve the sales target. Business situation analysis and Customer needs and wants analysis need to be conducted. Business situation analyses were conducted by analyze Porter’s Six Forces and Ansoff Matrix. Customer needs and wants analysis was conducted by Quality Function Deployment (QFD) method. Based on above analyses, the root causes are PT SOLARE were unable to fulfill the customer need for a product that able to operate in wide battery fluctuation, the selection height of the product according to the provision, and a low temperature LED lamp. Objective of this research is to give a recommendation proposed design of street lighting system for PT SOLARE, suggestion for adding more production lines, some suggestion price from target profit pricing method for the minimal product sales per month for PT SOLARE to get the break-even-point (BEP) and an implementation plan to manufacture the product. These recommendations are expected to help PT SOLARE to achieve the target sales. Keywords: Quality Function Deployment (QFD), Solar Street Lighting System, New Product Development.